First evidence for temperature’s influence on the enrichment, assembly, and activity of polyhydroxyalkanoate-synthesizing mixed microbial communities - Trego, Anna; Palmeiro-Sánchez, Tania; Graham, Alison; Ijaz, Umer Zeeshan; O’Flaherty, Vincent (Frontiers in Systems Biology, 2024)
Polyhydroxyalkanoates (PHA) are popular biopolymers due to their potential use as biodegradable thermoplastics. In this study, three aerobic sequencing batch reactors were operated identically except for the temperatures, which were set at 15°C, 35°C and 48°C. The reactors were subjected to a feast-famine feeding regime, where carbon sources are supplied intermittently, to enrich for PHA-accumulating microbial consortia. The biomass was sampled for 16S rRNA gene amplicon sequencing of both DNA (during the enrichment phase) and cDNA (during the enrichment and accumulation phases). All temperatures yielded highly-enriched PHA-accumulating consortia. Thermophilic communities were significantly less diverse than those at low or mesophilic temperatures. In particular, Thauera was highly adaptable, abundant and active at all temperatures. Low-temperatures resulted in reduced PHA production rates and yields. Analysis of the microbial community revealed a collapse of community diversity during low-temperature PHA accumulation, suggesting that the substrate dosing strategy was unsuccessful at low temperatures. This points to future possibilities for optimizing low-temperature PHA accumulation.The replacement of conventional plastics with more sustainable options, such as PHA, currently depends reducing PHA production costs. Mixed culture cultivation has become a popular alternative to conventional pure culture production. Moreover, mixed cultures allow for the use of wastewater as a potential substrate, an idea which has gained a lot of research attention. Although temperature is a key parameter, temperature comparisons and their effects on the microbial community dynamics and biosynthesis of PHA remain under-explored. Here, we report on the Deleted: potential of PHA to replace conventional plastics 52 Deleted: on them becoming more cost-competitive -53 Deleted: To this end, 54 Deleted: msuccessful cultivation of PHA-synthesizing mixed microbial communities at three distinct temperatures, but we also describe how temperature influences diversity, and assembly processes for particular genera (particularly those making up the core microbiome). Moreover, this is the first time, of which we are aware that the genus Thauera has been reported to accumulate PHA under such broad temperature ranges. Finally, using cDNA we were able to pinpoint the active PHA accumulating community and suggest strategies for optimizing low-temperature PHA production.